Ответы и объяснения

2013-10-25T18:07:40+00:00
5(х-9)=-2
5x - 45 = -2
5x = -2 + 45
5x = 43
x = 8,6

3=4(х+2)
3  = 4x  +8
3 - 8  =4x
-5 = 4x
x = -1,25

-7=5(х+5)
-7 = 5x + 25
-7 - 25 = 5x
-32  =5x
x = -6,4

9=5(х+9)
9 = 5x  +45
9  -45 = 5x
5x = -36
x = -7,2

7(х-1)=3х

7x - 7 = 3x
7x  -3x = 7
4x = 7
x = 1,75
2013-10-25T18:20:42+00:00
5(х-9)=-2
5x - 45 = -2
5x = -2 + 45
5x = 43
x = 8,6

3=4(х+2)
3  = 4x  +8
3 - 8  =4x
-5 = 4x
x = -1,25

-7=5(х+5)
-7 = 5x + 25
-7 - 25 = 5x
-32  =5x
x = -6,4

9=5(х+9)
9 = 5x  +45
9  -45 = 5x
5x = -36
x = -7,2

7(х-1)=3х

7x - 7 = 3x
7x  -3x = 7
4x = 7
x = 1,75